Medical and Surgical Treatment of Parathyroid Diseases An Evidence-Based Approach - Stack, Jr., Brendan C.; Bodenner, Donald L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text is an accessible and user-friendly guide, addressing the key points of parathyroid diseases. It presents a comprehensive treatment of parathyroid diseases as well as hundreds of high quality images and illustrations. Written and edited by respected leaders in the field of parathyroid diseases, this book aids in the comprehension of innovative concepts and focuses on the latest in clinical research and evidence based practices. Written for endocrine, head and neck, and general surgeons at various stages of experience, Medical and Surgical Treatment of Parathyroid Diseases includes chapters dedicated to parathyroid anatomy, physiology, and embryology, medical therapy for parathyroid disease (indications and pharmacotherapy), diagnostic imaging, surgical treatments, and special topics such as health services and healthcare economics related to parathyroid surgery.
Part 1. Introduction -- Evidence Based Medicine: Basic Concept and its Importance in the Medical Literature -- EBM Approach and Classification -- Part 2. Parathyroid Anatomy, Physiology, and Embryology -- Anatomy and Embryology -- Physiology and Molecular Biology -- Part 3. Parathyroid Diseases -- Single Gland Primary Hyperparathyroidism, Classic and Early Disease -- Multiple Gland Primary Hyperparathyroidism, MEN I and II -- Secondary Hyperparathyroidism -- Tertiary Hyperparathyroidism -- Part 4. Medical Therapy for Parathyroid Disease (Indications and Pharmacotherapy) -- Hypercalcemia -- Hyperparathormonemia, Analogs and Inhibitors -- Natural History of Untreated HPT -- Hypoparathyroidism -- Part 5. Parathyroid Diagnostic Imaging -- Tc99 Sestamibi -- Ultrasound -- CT, Including 4D -- Advanced Imaging, MRI -- Selective Angiography -- Part 6. Surgical Treatment of Parathyroid Disease -- Minimally Invasive Radioguided Parathyroidectomy -- Endoscopic Parathyroidectomy -- Unilateral Neck Exploration -- Bilateral Neck Exploration -- Surgery for Known Multi-Gland Parathyroid Disease -- Intra-operative PTH Assay -- Intra-operative Ultrasonography -- Re-operative Parathyroid Surgery -- Surgery for Ectopic Parathyroids -- Robotic Parathyroidectomy -- Part 7.Special Topics -- A History of Hyperparathyroidism -- Primary Hyperparathyroidism: Current Management Guidelines -- Osteoporosis -- Pathology -- Parathyroid Carcinoma -- Calciphylaxis -- Familial Hypocalcuric Hypercalcemia (FHH) Genetic Testing and Counseling for Hyperparathyroidism -- Parathyroid Cryopreservation and Autotransplantation -- Treatment for Hypoparathyroidism, to Include Stem Cell Therapy -- Intraoperative Nerve Monitoring for Parathyroid Surgery -- Outpatient Parathyroidectomy -- Cognitive Impact of Hyperparathyroidism -- Health Services and Healthcare Economics Related to Hyperparathyroidism and Parathyroid Surgery -- Technician Considerations for Parathyroid Imaging -- Radiation Safety in Parathyroid Imaging -- Laboratory Testing, PTH Measurement of Needle Aspirates, Intra Operative PTH Technologies -- Coding and Re-imbursement for Outpatient e/m and Procedures and Parathyroid Surgery -- Parathyroid Research with Multicenter Databases -- Parathyroid Disease, Diagnosis and Management: An International Perspective -- Complications in Parathyroid Surgery.
Keywords: Medicine; Oncology; Otolaryngologic surgery; Medicine & Public Health; Head and Neck Surgery; Oncology